Factors that affect the Amaount of Catfish Farming Production in the Catfish Village Boyolali Regency - Ariyanto, Nanda Bagus; Setyowati, Eni (Jurnal Ekonomi Balance, 2023)
The purpose of this study is to examine the influence of capital, land area, and labor on catfish farming production in Catfish Village, Palm Oil District, Boyolali Regency. Primary data was collected from 29 respondents over a period of one harvest quarter. The study results indicate that capital has a significant impact on catfish farming production, while land area and labor do not have a significant effect. These findings have important implications for catfish farmers and policymakers. It emphasizes the need for sufficient capital investment to enhance production capabilities. Policymakers can support farmers through financial programs and credit access to facilitate investment in modern technologies and infrastructure. It is important to note that this study focuses on the specific context of Catfish Village in Boyolali Regency. Further research is needed to validate these results and explore additional factors that may influence catfish farming production.